2021
DOI: 10.1007/s10664-021-09945-9
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of well-being and productivity among software professionals during the COVID-19 pandemic – a longitudinal study

Abstract: The COVID-19 pandemic has forced governments worldwide to impose movement restrictions on their citizens. Although critical to reducing the virus’ reproduction rate, these restrictions come with far-reaching social and economic consequences. In this paper, we investigate the impact of these restrictions on an individual level among software engineers who were working from home. Although software professionals are accustomed to working with digital tools, but not all of them remotely, in their day-to-day work, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
116
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(128 citation statements)
references
References 124 publications
9
116
1
2
Order By: Relevance
“…Critically, though, the potential effect for PA to influence job performance during work from home was not investigated [ 36 ], as was the case in our study. Furthermore, software professionals working from home during the pandemic reported that distractions, boredom, and the need for competence were negatively associated with self-reported job performance, but in contrast to our findings, there was no association between job performance and PA [ 37 ]. Our findings suggest that engagement in PA can support employee job performance in changing work environments, which is an important consideration for employers.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Critically, though, the potential effect for PA to influence job performance during work from home was not investigated [ 36 ], as was the case in our study. Furthermore, software professionals working from home during the pandemic reported that distractions, boredom, and the need for competence were negatively associated with self-reported job performance, but in contrast to our findings, there was no association between job performance and PA [ 37 ]. Our findings suggest that engagement in PA can support employee job performance in changing work environments, which is an important consideration for employers.…”
Section: Discussioncontrasting
confidence: 98%
“…Factors negatively affecting work ability have been identified as a lack of leisure time, vigorous PA, poor musculoskeletal health, older age, high mental work demands, and poor work environment [ 39 ]. During COVID-19, many employees were required to work from home, resulting in increased distractions and fewer peer-to-peer social interactions, potentially negatively affecting wellbeing during this time [ 5 , 37 ]. The pandemic also appears to have negatively impacted mental health, which could be a factor affecting work performance [ 1 , 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further complicating our typically held knowledge regarding employee engagement and the place of work is recent research that confirms how working from home during the COVID-19 pandemic was (for some) effective [26] and improved employee productivity and well-being [27]. The same has been reported in pre-COVID-19 studies [28,29].…”
Section: Introductionmentioning
confidence: 80%
“…The majority of Indian information technology (IT) companies have resorted to rigorous employee performance metrics and massive retrenchment and pay cuts amid the pandemic (Mohapatra, 2020 ). Furthermore, since the pandemic, increased workload and working hours have caused considerable stress among software professionals (Russo et al, 2021 ). Such an increased level of stress, coupled with anxiety and concerns regarding the COVID-19 pandemic, makes it crucial to effectively manage the psychological capital and well-being of the IT workforce.…”
Section: Introductionmentioning
confidence: 99%